Teaching character education to socially alienated children through puppetry primary level - Fonacier, Arcenia O. 1936-
The study proposed activities for character education for the socially-alienated children with the use of puppets. The study aims to know the goals of character education to socially-alienated children, th methods by which puppetry can be used as a means to achieve the goals in character education for the socially-alienated, and the activities in character education for the socially-alienated. This paper is accomplished along the research training scheme.